Saliva as a diagnostic sample of SARS-CoV-2: an integrative review - Nogueira, Bruna de Paula; Orcina, Bernardo da Fonseca; Oliveira, Rodrigo Cardoso de; Santos, Paulo Sérgio da Silva (Revista Uningá, 2022)
In March 2020, the disease caused by the new coronavirus (SARS-CoV-2) was characterized as a pandemic. Due to the magnitude that the disease has reached and its unprecedented character, a growing scientific interest in the disease has emerged, with searches to find new diagnostic methods, increasing the speed to obtain test results and, consequently, a better epidemiological mapping of the disease. This integrative review aims to analyze the main scientific evidence on the use of saliva as a diagnostic method for COVID-19. In the present integrative review, searches were conducted in four electronic databases in March 2022, namely: PubMed, in which results were included exclusively in English, and in the platforms Google Scholar, SciELO and Virtual Health Library (VHL), with the inclusion of results strictly in Portuguese. Different keywords were used according to the dominant language of the databases, being in PubMed in English language chosen ''SARS-CoV-2'', ''saliva'', ''diagnosis'', ''viral load'' and ''coronavirus COVID-19'' and in the other platforms, in Portuguese language ''saliva'', ''covid'' and ''diagnosis''. Among the 45 articles included and analyzed, more than half classified saliva as an alternative or complementary diagnostic method. Yet, only three articles out of the total number classified saliva as an unviable sample for diagnostic testing. Thus, saliva showed positive results as a diagnostic option and for COVID-19 follow-up and monitoring. However, despite the limitations of the studies, the saliva sample in pediatric patients suggests having low sensitivity.